(untitled) (Communications in Mathematical Research, 2023)
In this paper, we analyze the large time behavior of nonnegative solutions to the doubly nonlinear diffusion equation u_t−div(|∇u^m|^p−2∇u^m)=0 in R^N with p>1, m>0 and m(p−1)−1>0. By using the finite propagation property and the L^1-L^∞ smoothing effect, we find that the complicated asymptotic behavior of the rescaled solutions t^μ/2u(t^β_·,t) for 0